Efficacy and Safety of Pyrotinib Versus T-DM1 in HER2+ Metastatic Breast Cancer Patients Pre-Treated With Trastuzumab and a Taxane: A Bayesian Network Meta-Analysis - Liao, Hao; Huang, Wenfa; Liu, Yaxin; Pei, Wendi; Li, Huiping (Frontiers in Oncology, 2021)
Purpose: To compare the efficacy and safety between pyrotinib (Pyr) and trastuzumab emtansine (T-DM1) in pre-treated human epidermal growth factor receptor 2-positive (HER2+) metastatic breast cancer (MBC) patients. Methods: A comprehensive literature search of the PubMed, EMBASE, and Web of Science was performed in August 2020. Randomized clinical trials comparing the efficacy and safety between different anti-HER2 regimens in patients pre-treated with trastuzumab (Tra) and a taxane in metastatic settings (≤ second-line treatment) were included. A fixed effects network meta-analysis based on the Bayesian inferential framework was conducted for progression-free survival (PFS), overall survival (OS), overall response rate (ORR), and grade≥3 adverse events (AEs). Values of surface under cumula¬tive ranking probability curve (SUCRA) were calcu¬lated to offer a ranking of all regimens. Results: Twelve studies with 4353 subjects were identified. Nine regimens were included into the network: T-DM1, lapatinib-capecitabine (Lap-Cap), Tra-Cap, Cap, neratinib (Ner), pertuzumab (Per)-Tra-Cap, Pyr-Cap, atezolizumab (Ate)-T-DM1, and Ner-Cap. For PFS, Pyr-Cap was more favorable than T-DM1 (hazard ratio, 95% confidence interval: 0.77, 0.70-0.86), Lap-Cap (0.64, 0.59-0.69), Tra-Cap (0.63, 0.56-0.70), Cap (0.50, 0.45-0.56), Ner (0.59, 0.51-0.69), Per-Tra-Cap (0.68, 0.59-0.79), and Ner-Cap (0.72, 0.64-0.81). For OS, Pyr-Cap showed further improvement than Lap-Cap (hazard ratio, 95% confidence interval: 0.71, 0.52-0.99), Cap (0.68, 0.49-0.96), and Ner (0.65, 0.45-0.94). For ORR, Pyr-Cap was significantly superior than Cap (odds ratio, 95% confidence interval: 7.87, 1.22-56.51). No significant difference was observed in grade≥3 AEs among all the regimens. Pyr-Cap ranked in the highest in PFS, OS, ORR, and grade≥3 AEs (SUCRA = 99.4%, 89.7%, 86.4%, and 89.3%). Conclusions: These results indicate that Pyr may be more effective than T-DM1 in HER2+ MBC patients pre-treated with Tra and a taxane. However, it may be associated with more grade≥3 AEs.